BUB1 an Overexpressed Kinase in Sarcoma: Finding New Target Therapy for Osteosarcoma, Liposarcoma, Synovial Sarcoma, and Leiomyosarcoma - Mercedes Olvera-Valencia; Fernando Luna-Maldonado; Joselyn Juarez-Reyes; Alejandro Lopez-Saavedra; Jossimar Coronel-Hernandez; Oliver Millan-Catalan; Daniel Guzman-Gomez; Frida Rodríguez-Izquierdo; Luis A. Herrera; David Francisco Cantú-De León; Carlos Perez-Plasencia; Eloy-Andres Pérez-Yepez (Biomolecules)
Sarcomas are heterogeneous mesenchymal tumors, and their pharmacological treatment remains challenging due to the high toxicity and poor efficacy of current therapies. This study aimed to identify common overexpressed kinases in the four most frequent sarcoma subtypes to establish novel therapeutic targets. A bioinformatics approach using patient-derived gene expression data sets identified overexpressed kinases shared across these sarcoma types. Later, BUB1 was determined as the kinase consistently overexpressed across the osteosarcoma, liposarcoma, leiomyosarcoma, and synovial sarcoma. Moreover, the role of this kinase was further validated through molecular and functional assays, including pharmacological inhibition in cell lines derived from the four sarcoma subtypes. BUB1 inhibition reduced the phosphorylation of AKT and H2A proteins, precluded cell proliferation, and inhibited colony formation in sarcoma cells. Finally, overall survival analysis highlighted a strong correlation between high BUB1 expression and poorer survival rates in sarcoma patients. Altogether, these findings underscore the potential of BUB1 as a therapeutic target and prognostic marker in sarcomas. Targeted inhibition of BUB1 may provide a novel strategy to reduce tumor growth and improve outcomes for patients with bone and soft tissue sarcomas.